2022
DOI: 10.1155/2022/2295044
|View full text |Cite|
|
Sign up to set email alerts
|

LncRNA-PAX8-AS1 Silencing Decreases Cell Viability, Enhances Apoptosis, and Suppresses Doxorubicin Resistance in Myeloid Leukemia via the miR-378g/ERBB2 Axis

Abstract: Objective. Considering the role of lncRNAs reported as regulators in acute myeloid leukemia (AML) progression, the current research aims to investigate the role of PAX8-AS1 in chemo-resistant AML. Methods. Human AML cells HL60 and human doxorubicin (ADM)-resistant AML cells (HL60/ADM cells) were used to establish in vitro models of chemo-sensitive AML and refractory/recurrent AML, respectively. CCK-8 assay and flow cytometry were used to determine cell resistance to ADM, viability, and apoptosis. PAX8-AS1, miR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%